Portrait of Election Violations: Damage of Political Party Attributes, Elimination of Voting Rights and Obstruction of Campaigns, Perspective of Election Law No. 7 of 2017 - Rahmatiah, Rahmatiah; Sahi, Yayan; Noprianto, Noprianto; Triadityansya, Moh; Sabidullah, Nurhazrawaty (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This research aims to analyze a portrait of election violations in 2024, with a focus on damaging political party attributes (APK), eliminating voting rights, and obstructing campaigns in the context of Law Number 7 of 2017 concerning General Elections in Gorontalo City. The method used in this study is liberty research, which includes literature review, analysis of official documents, case studies, and review of statutory regulations. Data collection techniques include study of books, scientific articles, reports from Bawaslu and KPU, as well as mass media news. Research findings show that the main violations consist of the practice of money politics, destruction of APKs, elimination of voting rights, and obstruction of campaigns. The practice of money politics, which includes bribery and vote buying, dominates with an incidence rate of 64%, followed by PK damage at 18%, removal of voting rights at 9%, and campaign obstruction also at 9%. Even though Law Number 7 of 2017 stipulates strict sanctions against money politics, this practice remains rampant and damages the integrity of elections. Apart from that, destruction of APKs, elimination of voting rights, and obstruction of campaigns are also significant issues that affect the fairness of elections. This research concludes that more effective efforts are needed from all parties related to election organizers, supervisory institutions and the public to deal with these violations and ensure the implementation of cleaner and more democratic elections.